2021
DOI: 10.1007/s10668-021-01477-y
|View full text |Cite|
|
Sign up to set email alerts
|

Quantifying carbon footprint for ecological river restoration

Abstract: RIVER restoration is a popular technique to rehabilitate degraded river habitat. Given the nature of these types of engineering projects, using ecological indicators to monitor the restoration effectiveness has been a traditional approach. However, as this approach emphasizes the post-project performance, environmental impact attributed to a project’s construction phase has received little attention directly or indirectly. This study quantified the carbon footprint of ecological river restoration, using a proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…It is important to note that the results reported here only offer a coarse perspective on the positive influence of ecological restoration on CO 2 emission mitigation in polluted urban rivers because they do not differentiate the effects of various restoration measures and do not cover whole‐stream carbon metabolism. Given the widespread CO 2 supersaturation, local physical aeration in river channels can degas a mass of CO 2 and CH 4 (Chiu et al., 2021), which would increase the CO 2 emissions from restored rivers. Meanwhile, previous studies suggested that many engineered microorganism inputs during nutrient removal could strongly alter the microbial flora structure and carbon metabolism in urban rivers, resulting more CO 2 and CH 4 production in the water column (Rafeeq et al., 2023; Sharma et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the results reported here only offer a coarse perspective on the positive influence of ecological restoration on CO 2 emission mitigation in polluted urban rivers because they do not differentiate the effects of various restoration measures and do not cover whole‐stream carbon metabolism. Given the widespread CO 2 supersaturation, local physical aeration in river channels can degas a mass of CO 2 and CH 4 (Chiu et al., 2021), which would increase the CO 2 emissions from restored rivers. Meanwhile, previous studies suggested that many engineered microorganism inputs during nutrient removal could strongly alter the microbial flora structure and carbon metabolism in urban rivers, resulting more CO 2 and CH 4 production in the water column (Rafeeq et al., 2023; Sharma et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The process of stream restoration implementation has a non-zero carbon footprint, estimated by Chiu et al (2022) as 9-14 kg CO 2 per meter of stream restored. However, ecological restoration can transform the relative proportions of landscapes considered as carbon sources versus sinks and provide significant capacity to more efficiently sequester, rather than emit, carbon over decadal timescales (Zhou et al, 2020).…”
Section: Human Alterations and Restoration Of Floodplain Carbon Stocksmentioning
confidence: 99%
“…Recent studies have considered the carbon footprint of ecological restoration projects through the LCA approach. For example, Chiu et al (2021) conducted a framework for the carbon footprint of ecological restoration project in California. For landscaping hard work, Lin and Lin (2022) established an embodied carbon database in Taiwan based on the LCA concept.…”
Section: Introductionmentioning
confidence: 99%